The Method of Da’wah of Jama’ah Mastūrah in Increasing Religious Awareness of Women in Aceh Besar - Wirman Wirman; Mira Fauziah (Universitas Islam Negeri Sultan Syarif Kasim Riau, 2020)
Jama’ah Mastūrah refers to a congregation of women division of Jama’ah Tabligh. As is the case of the male counterpart, Jama’ah Mastūrah also takes part in Islamic missionary activities. However, this group does not carry out da’wah in an open space or in front of the congregation. This study aimed to analyze the method of da’wah carried out by Jama’ah Mastūrah in raising women religious awareness in Aceh Besar. The study used qualitative approach and the descriptive analysis method. Data were collected by interview and documentation study. The results showed that the da’wah method carried out by Jama'ah Masṭurah was the method of da’wah bi al-lisān, bi al-kitābah and bi al-hāl. The bi al-lisān method is carried out by inviting the surrounding community to invite people to pray, wear a headscarf, recite the Qur'an and attend ta'lim activities in their homes. The bi al-kitābah is a method of da’wah by means of written materials, such as books, billboards, banners, bulletin boards, or pamphlets, containing messages of da’wah to mad’ū. The bi al-hāl method is carried out by showing noble morals, maintaining the limits of the genitals and avoiding meeting with men who are not mahram.